1996
DOI: 10.1001/archneur.1996.00550010084020
|View full text |Cite
|
Sign up to set email alerts
|

A Door-to-Door Survey of Parkinson's Disease in a Chinese Population in Kinmen

Abstract: The prevalence rates of PD in Kinmen were much higher than those reported from mainland China, but slightly lower than those reported from more developed countries. The present findings suggest that, instead of genetic factors, differences in case-ascertainment, life expectancy, and the length of survival with PD may be more important contributors to the variations in observed PD prevalence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 25 publications
10
66
2
Order By: Relevance
“…It is important to note that all marriages of Gypsies are only to other Gypsies, so they exist as genetic isolates. As Gypsies' origin is Asian [15], they would be expected to have a lower prevalence of PD, if genetic factors are responsible for the reported lower prevalence in the Asian population [4][5][6]21]. The estimated prevalence rate in this study for PD in Gypsies is comparable to that reported for the Asian population [4].…”
Section: Discussionsupporting
confidence: 54%
“…It is important to note that all marriages of Gypsies are only to other Gypsies, so they exist as genetic isolates. As Gypsies' origin is Asian [15], they would be expected to have a lower prevalence of PD, if genetic factors are responsible for the reported lower prevalence in the Asian population [4][5][6]21]. The estimated prevalence rate in this study for PD in Gypsies is comparable to that reported for the Asian population [4].…”
Section: Discussionsupporting
confidence: 54%
“…This range is in line with our overall estimate. Studies from other parts of the world (USA, China and Argentina) have reported prevalence rates between 107 and 867 per 100,000 individuals [17,18,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent community surveys had often found a high percentage of new cases. In the Kinmen study [18], all subjects were examined by neurologists and the percentage of new cases was as high as 78% (18 of 23). This result is also echoed by another community study in which all were examined [1].…”
Section: Discussionmentioning
confidence: 99%